An Observational Study of Teaching Methods in Secondary School Science Classrooms - Edidiong E. Ukoh; Adeniyi Michael Adeduyigbe; Alice M. Olagunju (Scientia Publica Media, 2026)
Science education plays a critical role in developing learners’ problem-solving, inquiry, and critical thinking skills. However, despite calls for student-centered and technology-enhanced methods, teacher-centered methods, particularly lecture-based instruction, still dominate the science classroom. While such methods ensure curriculum coverage, they often limit opportunities for active engagement, collaboration, and deeper conceptual understanding. This study, therefore, investigates the teaching methods most commonly used in secondary school science classrooms, examining the prevalence of teacher-centered, student-centered, and technology-enhanced instructional strategies. The instrument used was the Science Classroom Instruction Observation Sheet (SCIOS). Data were collected from 80 observed lessons in public and private schools. The findings revealed that lecture-based instruction dominates science classrooms, while student-centered methods such as small-group discussions, desk work, and student presentations remain infrequent, rarely exceeding five observations per interval. Additionally, technology-enhanced strategies, including multimedia and digital simulations, were among the least observed, appearing in fewer than three intervals on average. The heavy reliance on teacher-centered instruction, while effective for content delivery, raises concerns about its impact on student engagement and inquiry-based learning. These findings emphasize the need for a more balanced instructional approach that integrates interactive, student-driven strategies to enhance science education.